About the use of nano-therapeutic means in medicine (ro.) - Romeo T. Cristina; Andreia B. Chirila (Medicamentul Veterinar)
Nanobiotehnology is a relatively new field of research, being the interface between the life sciences and nanotechnology. In this area where the work dimensions are between 1 nm and 100 nm the recovery of biomolecules’ quality and the processes involved it is proposed, in the development of materials or devices with certain medical activity. This bibliographic approach proposes a first foray into nano-therapeutic resources use in the medical field. Are presented sintheticaly the main nanomaterials, their properties and potential applications in nanomedicine, magnetic fluids, their synthezis and stabilization as well as recent advances in this topic.